Percepção do psicólogo sobre a assistência psicológica ao paciente com Covid-19 em unidade de terapia intensiva - Moraes, Andrea Silva (2021)
Critically ill patients with Covid-19 admitted to the Intensive Care Unit regularly need to use mechanical ventilation as life support. Orotracheal intubation limits patient communication through speech, which can lead to anxiety, low mood and/or depression. The role of the psychologist should not be restricted to patients who are able to express themselves in terms of their psychological and emotional needs through speech, but rather provide the intubated patient with emotional and psychic expression, in addition to welcoming their perceptions, regarding the treatment and experience of hospitalization. Objective to analyze the perception of psychology professionals about their practice in the Intensive Care Unit, with critically ill patients diagnosed with Covid-19. Method: descriptive cross-sectional observational study, with psychologists working with patients with Covid-19 in intensive care units, in hospitals located in a Brazilian capital. Sociodemographic variables were used: age, sex and marital status; also education and professional performance: place of higher education/graduation, time of basic education, specialization and time of practice in a hospital unit and specifically in ICUs, and self-perception about the experience of professional practice was evaluated. Data collection was performed remotely, with the application of a sociodemographic questionnaire and the Free Word Association Technique (TALP) instrument to assess self-perception. Four phrase-type stimuli were chosen for TALP: Stimulus1- Patient admitted to an isolation infirmary. Stimulo2- Conscious and oriented patient admitted to the intensive care unit. Stimulus3- Patient under mechanical ventilation (MV) in the intensive care unit. Stimulus4- Considering the pandemic and my work with the patient diagnosed with Covid-19, I feel. Data analysis was performed using the Excel program (2016) and the Tri-Deux-Mots application (version 5.1) which performs factor analysis by correspondence and presents the results in spatial quadrants. Results: 59 psychologists participated, 66.1% of them aged between 24 and 35 years old, 86.5% female and 59.3% with a partner; 86.5% were trained in private institutions in the years 2014 to 2020, proportion of 52.5% and 47.5% are specialists in Health and Hospital Psychology. Practice in the ICU with experience of less than one year was 35.6% and 37.3% with hospital practice for between one and four years. The most common words when considering the experience of psychological care with the patient with Covid-19 in the infirmary (stimulus 1) were: anguish, anxiety, isolation, fear and loneliness. With conscious patients in the ICU (stimulus2) were: anxiety, anguish, fear and with patients on MV (stimulus 3) were: anxiety, severity, death, fear and family. In addition to the psychologists expressing (stimulus 4) feeling anxiety, anguish and fear as the most present psychic symptoms at this time when working with patients with Covid-19. Conclusion: the psychologist expressed concern with the patient and possible outcomes, such as death, and with their families, given the delicacy and uncertainty in this type of hospitalization. In addition to being concerned about the physical condition and worsening of the clinical condition of the ventilating patient. The word “tiredness” reflected new habits and work routines, a high demand coming not only from patients and family members, but also from the team and peers, in the face of the unknown.